A review on application of gold nanostructures in cancer therapy - Maryam Heidari; Naghmeh Sattarahmady (Basic & Clinical Cancer Research, 2015)
Today, use of nanotechnology for cancer therapy is an active field of research. Early detection, accurate diagnosis, and individual treatment are the aims which cause nanotechnology as an attractive area for research. Among metallic nanomaterials, gold nanostructures have unique properties which make them remarkable candidates for biomedical approaches. Surface plasmonic resonance (SPR) effect of gold nanostructures leads to a maximum absorption in a particular electromagnetic wavelength. This wavelength changes with shape and size of the particles, so optical properties of gold nanostructures are adjustable. In this review, we will summarize the application of gold nanostructures in treatment of cancer especially as the agent in Plasmonic photothermal therapy (PPTT) and photosensitizer in photodynamic therapy (PDT).